The Impact of Lab4 Probiotic Supplementation in a 90-Day Study in Wistar Rats - Webberley, Thomas S.; Masetti, Giulia; Baker, Laura M.; Dally, Jordanna; Hughes, Timothy R.; Marchesi, Julian R.; Jack, Alison A.; Plummer, Sue F.; Ramanathan, Guru; Facey, Paul D.; Michael, Daryn R. (Frontiers in Nutrition, 2021)
The anti-inflammatory and cholesterol lowering capabilities of probiotic bacteria highlight them as potential prophylactics against chronic inflammatory diseases, particularly cardiovascular disease. Previous studies in silico, in vitro and in vivo studies suggest that the Lab4 probiotic consortium may harbour such capabilities and in the current study, we assessed plasma levels of cytokines/chemokines, short chain fatty acids and lipids and faecal levels of bile acids in a subpopulation of healthy Wistar rats included in 90-day repeat dose oral toxicity study. In the rats receiving Lab4, circulating levels of pro-inflammatory interleukin-6, tumour necrosis factor-α and keratinocyte chemoattractant/growth regulated oncogene were significantly lower compared to the control group demonstrating a systemic anti-inflammatory effect. These changes occurred alongside significant reductions in plasma low density lipoprotein cholesterol and increases in faecal bile acid excretion implying the ability to lower circulating cholesterol via the deconjugation of intestinal bile acids. Correlative analysis identified significant associations between plasma tumour necrosis factor-α and the plasma total cholesterol:high density lipoprotein cholesterol ratio and faecal levels of bifidobacteria in the Lab4 rats. Together, these data highlight Lab4 supplementation as a holistic approach to CVD prevention and encourages further studies in humans.